Pelatihan Penerapan Konvensi Hak (KHA) Anak Dan Satuan Pendidikan Ramah Anak (SRA) di Madrasah - Nasarudin; Husnan (EDUPEDIA Publisher, 2023)
State Islamic Primary School 1 Mataram has gained the trust to implement a child-friendly education unit policy in an effort to improve the implementation of learning that is committed to create a pleasant, safe, comfortable school environment without discrimination, intimidation, or violence in the Islamic school environment. And fulfill children's rights in every aspect of life in a planned and responsible manner. The purpose of the activity is to increase madrasah teachers' understanding of children's rights in child-friendly schools through seminars and interactive discussions held on May 25, 2023. The implementation of this activity consists of three stages: preparation, seminar activities, and closing and follow-up. The teachers of Islamic school are increasingly aware of the urgency of the Convention on the Rights of the Child and child-friendly schools, so they are willing to continue with the implementation of inclusive madrasah.